Adipose tissue‐derived mesenchymal stem cells' acellular product extracellular vesicles as a potential therapy for Crohn's disease. Issue 7 (6th May 2022) - Altemus, Jessica; Dadgar, Neda; Li, Yan; Lightner, Amy L.
Abstract: The breakdown of gastrointestinal tract immune homeostasis leads to Crohn's disease (CD). Mesenchymal stem cells (MSCs) have demonstrated clinical efficacy in treating CD in clinical trials, but there is little known about the mechanism of healing. Considering the critical roles of macrophage polarization in CD and immunomodulatory properties of MSCs, we sought to decipher the interaction between adipose‐derived MSCs and macrophages, including their cytokine production, regulation of differentiation, and pro‐/anti‐inflammatory function. RNA extraction and next generation sequencing was performed in adipose tissue from healthy control patients' mesentery ( n  = 3) and CD mesentery ( n  = 3). Infiltrated macrophage activation in the CD mesentery was tested, MSCs and extracellular vesicles (EVs) were isolated to compare the regulation of macrophage differentiation, cytokines production, and self‐renewal capacities in vitro. CD patients' mesentery has increased M1 macrophage polarization and elevated activation. MSCs and their derived EVs, isolated from inflamed Crohn's mesentery, leads to a rapid differentiation of monocytes to a M1‐like polarized phenotype. Conversely, MSCs and their derived EVs from healthy, non‐Crohn's patients results in monocyte polarization into a M2 phenotype; this is seen regardless of the adipose source of MSCs (subcutaneous fat, omentum, normal mesentery). EVs derived from MSCs have the ability to regulate macrophage differentiation. Healthy MSCs and their associated EVs have the ability to drive monocytes to a M2 subset, effectively reversing an inflammatory phenotype. This mechanism supports why MSCs may be an effective therapeutic in CD and highlights EVs as a novel therapeutic for further exploration. Abstract : Chron's diseased mesenteric mesnechymal stem cells and associated extracellular vessicals polarize macrophages to an inflammatory M1 phenotye.